2020
DOI: 10.3390/app10217579
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Analysis of Large Diameter Monopiles of Offshore Wind Turbines under Scour

Abstract: The displacement of monopile supporting offshore wind turbines needs to be strictly controlled, and the influence of local scour can not be ignored. Using p–y curves to simulate the pile–soil interaction and the finite difference method to calculate iteratively, a numerical frame for analysis of lateral loaded pile was discussed and then verified. On the basis of the field data from Dafeng Offshore Wind Farm in Jiangsu Province, the local scour characteristics of large diameter monopile were concluded, and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Its soil-structure interaction modeling techniques have been reviewed by many scholars and extensively used for the analysis and design of OWTs. 17,25,46,[49][50][51][52][53] Although different modeling techniques require different input parameters, the determination of parameters for each model is based on the procedures widely accepted in engineering practice to represent the same physical problem. Therefore, the common goal of each model is the same.…”
Section: Dynamic Soil Structure Interaction Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its soil-structure interaction modeling techniques have been reviewed by many scholars and extensively used for the analysis and design of OWTs. 17,25,46,[49][50][51][52][53] Although different modeling techniques require different input parameters, the determination of parameters for each model is based on the procedures widely accepted in engineering practice to represent the same physical problem. Therefore, the common goal of each model is the same.…”
Section: Dynamic Soil Structure Interaction Modelsmentioning
confidence: 99%
“…2,[18][19][20][21] A largediameter (3−10 m) monopile is a common choice for the foundation of modern offshore wind turbines, but the widely used approach (p-y curve method), as specified in American Petroleum Institute (API) guidelines 22 or Det Norske Veritas (DNV) guidelines, 23 may not be suitable for such large piles. [24][25][26] This is because the p-y, t-z, and q-z curves recommended by API or DNV were calibrated against the response of small-diameter (610 mm) slender piles (length-to-diameter ratio of ∼34) for offshore oil and gas structures. The behavior of large monopiles is like rigid body rotation and displacement, 0.0 0.5 which is different from conventional bending piles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] In 2020, Sajjad tested two fixed-type foundations, one of them is monopile, and the other is a jacket [17]. Using (p-y) curves, in 2020, Zhaoyao Wang et al researched rigorously controlling the displacement of monopile offshore wind turbines, not ignoring the influence of local scour [18]. In 2021, Jianhua Zhang et al suggested a method for the dynamic response of offshore structures by combining segmented responses is proposed, which depends on the pole-residue method to calculate those segmented responses.…”
Section: Introductionmentioning
confidence: 99%
“…This composite foundation is initiated from the concept of pile caps and embedded retaining walls with stabilizing platforms, in which the addition of the circular wheel increases the shear stress and restoring moment against the lateral deflection [13][14][15]. The combined wheel can also be applied as an effective reinforcement for existing monopiles to provide additional bearing capacities and protections of the seabed from circum-pile scouring [15][16][17].…”
Section: Introduction 1conceptmentioning
confidence: 99%